The dynamics of Andromeda's dwarf galaxies and stellar streams. Issue Volume 11:Issue S321(2015) (21st March 2017) - Collins, Michelle L. M.; Rich, R. Michael; Ibata, Rodrigo; Martin, Nicolas; Preston, Janet; ,
Abstract: As part of the Z-PAndAS Keck II DEIMOS survey of resolved stars in our neighboring galaxy, Andromeda (M31), we have built up a unique data set of measured velocities and chemistries for thousands of stars in the Andromeda stellar halo, particularly probing its rich and complex substructure. In this contribution, we will discuss the structural, dynamical and chemical properties of Andromeda's dwarf spheroidal galaxies, and how there is no observational evidence for a difference in the evolutionary histories of those found on and off M31's vast plane of satellites. We will also discuss a possible extension to the most significant merger event in M31 - the Giant Southern Stream - and how we can use this feature to refine our understanding of M31's mass profile, and its complex evolution.